European agreements for nature conservation need to explicitly address wolf-dog hybridisation. (August 2020) - Salvatori, Valeria; Donfrancesco, Valerio; Trouwborst, Arie; Boitani, Luigi; Linnell, John D.C.; Alvares, Francisco; Åkesson, Mikael; Balys, Vaidas; Blanco, Juan Carlos; Chiriac, Silviu; Cirovic, Dusko; Groff, Claudio; et al.
Abstract: Hybridisation between wolves and dogs is increasingly reported in Europe. Nonetheless, no systematic survey has ever been attempted at the continental scale. We made the first assessment of wolf-dog hybridisation (WDH) occurrence in Europe and analysed how the phenomenon is addressed by international legislation and managed at the country level. We found that WDH is reported in all nine extant European wolf populations, and in 21 out of 26 countries for which we received information. The two main international legal instruments (i.e., the Habitats Directive and the Bern Convention) do not explicitly mention the threat posed by hybridisation but do provide guidance promoting control of free-ranging wolf-dog hybrids. However, we recorded poor compliance with such recommendations in most European countries, and a lack of coordination in addressing WDH among countries sharing the same wolf population. Alarmingly, we revealed a lack of well-designed and implemented country-wide genetic surveys to detect and monitor hybridisation, both relevant pre-requisites to effectively implement WDH management. By recommending criteria for an operative definition of "hybrid", we also suggest improvements to enhance WDH-related policy at the European scale. Highlights: First Europe-wide assessment of wolf-dog hybridisation (WDH). Wolf-dog hybrids reported in 21 out of 28 countries surveyed. Few countries have policies compliant with Bern Convention Rec. 173/2014, which encourages removal of hybrids from the wild. Most management interventions are undertaken without reference to a clear national policy. Few countries prescribe national genetic monitoring for early detection of WDH.